Stroke in younger survivors : an investigation into their experiences and the impact of problem solving therapy on post stroke depression, anxiety, quality of life and problem solving abilities : a thesis presented in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology at Massey University, Wellington, New Zealand - Chalmers, Charlotte (Massey University, 2018)
Stroke affects approximately 6000 New Zealanders every year with approximately 25% of individuals with first ever stroke in New Zealand under 65 years old. Stroke survivors commonly experience post stroke depression, anxiety, and low quality of life, which impacts negatively on the rehabilitation process. Research has also shown that stroke survivors who have higher depression scores demonstrate more ineffective problem solving skills than stroke survivors with lower depression scores. There is limited research into the efficacy of non-pharmacological treatments for the experience of emotional distress following stroke. Research that is available provides promising results for the efficacy of problem solving therapy (PST) for treating post stroke depression in older stroke survivors, however there is no research on this or any form of psychotherapy with younger stroke survivors (18-65). The current research had two aims. The first was to collect information on problems experienced by younger (18-65) stroke survivors in New Zealand via a short online survey. Quantitative data was analysed using descriptive statistics and demonstrated that younger stroke survivors in New Zealand experience a number of different problems, with the most significant being difficulty with invisible disabilities. The qualitative analysis suggested large variability in how these problems affect the younger stroke survivors, and health professionals working with the younger survivors on their post stroke journey should take this into account. Using information gathered from the survey the second aim was to evaluate the efficacy of PST for reducing symptoms of depression and anxiety, and increasing effective problem solving skills and quality of life in younger stroke survivors (aged 18-65). Using a group intervention format PST was delivered in six sessions over six weeks.13 participants were recruited for the PST group, and this was compared with 16 participants who were originally placed on a wait-list control group (between-subject analysis). Once both groups had completed PST, the 28 participants were combined for within-subject analysis. For the between-subject analysis, measures at baseline (pre-waitlist/pre-baseline) were compared with post-waitlist/post-treatment measures. This demonstrated that PST was no more effective than being on a wait-list control group. However, the within-subject analysis (measures at baseline, at the final therapy session and at three-month follow up) demonstrated significant improvements on depression, anxiety and quality of life measures. Participants also rated the sessions and overall PST as helpful and enjoyable when asked to complete feedback forms. The main recommendation from this research is that the provision of education sessions post stroke that incorporate the stroke survivor and their families/support persons, would be beneficial. It is suggested that these be run after the acute phase, when stroke survivors are reintegrating back into the community. Information could be provided regarding what common symptoms are (both visible and invisible), how they may manifest, and beneficial ways for the stroke survivors and their family members to respond to these difficulties. It is also recommended that these sessions include speakers who are stroke survivors, and who have been through the post stroke journey. The speakers could talk about what they had experienced, what had been helpful and unhelpful to them, and what resources are accessible in the community. Finally, it is recommended that some form of support group be set up for younger stroke survivors in order to reduce the isolation that younger stroke survivors experience, however it remains unclear what type of support this should be, and future studies should be conducted to further explore this area. These studies could compare PST with social support groups, or other forms of therapy such as CBT to tease out what is actually beneficial to the younger stroke survivor.
Keywords: Cerebrovascular disease|xPatients|xRehabilitation; Problem-solving therapy; Clinical health psychology